Investigation of Backfill Compaction Effect on Buried Concrete Pipes (Journal of Engineering, 2013)
The present study deals with the experimental investigation of buried concrete pipes. Concrete pipes are buried in loose and dense conditions of gravelly sand soil and subjected to different surface loadings to study the effects of the backfill compaction on the pipe. The experimental investigation was accomplished using full-scale precast unreinforced concrete pipes with 300 mm internal diameter tested in a laboratory soil box test facility set up for this study. Two loading platforms are used namely, uniform loading platform and patch loading platform. The wheel load was simulated through patch loading platform which have dimensions of 254 mm *508 mm, which is used by AASHTO to model the wheel load of a HS20 truck. The pipe-soil systems were loaded up to pipes collapse. Pipes were instrumented with strain gauges to measure circumferential strains, in addition to dial gauges, for measurements of the pipe vertical deflections and settlement of the loading platforms. The test results indicated that flexure governed the buried pipe behavior. Flexural cracks formed slightly before the ultimate load. A comparison of soil backfill, between a loose and dense compaction, showed that the dense backfill improve largely the pipe installation and the strength ofpipe-soil system